St. Thomas Aquinas in Ukrainian Orthodox Schools - Sodomora, Pavlo (Hybris, 2019)
Ukrainian philosophical thought has been developing under the influence of several philosophical streams. Being influences by Orthodox tradition mainly, Church has always been at the forefront of any political campaign conducted on Ukrainian terrain. The level of education plays a key role in the process of cultural development of any country. Western part of Ukraine, comparing to its Eastern counterpart, had better access to education and information due to Catholic Church predominance in the region. The article intends to investigate the scholastic and patristic thought and its reproduction by Ukrainian cultural environment via various European teaching systems. Ukraine has been developing in a broad European context and this is why it could not have been deprived of influential teachings. But Russian imperialistic, and later communist ideology was hindering constantly the deployment and development of many ideas that were important for European philosophy. Together with Eastern theology, which was based mainly on works of Damascenus, Aristotelian traditions were introduced in Ukrainian schools gradually, and based on Aristotle’s works, theology of St. Thomas was taught. Prominent Ukrainian thinkers were influenced by many scholastic philosophers, including St. Thomas Aquinas. Aquinas’ influence is apparent in later thinkers.